2019
DOI: 10.3390/su11123476
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Mountain Farming in Norway

Abstract: The concept of socio-ecological farm resilience is used to understand how farmers manoeuvre in a context of change, what choices and priorities they make, and how that subsequently influences the development of the farming landscape. The author uses farm resilience, the capabilities of buffering, adaptation and transformation, and the response of bouncing back or forward as a conceptual frame in a study of farmers in a mountain community in Norway. Interviews were held with selected farmers. The results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Such studies often use in-depth interviews to ask farmers what disturbances they have perceived in the past, and how they have coped with and adapted to changes. Some studies have compared case studies from several countries (e.g., [63][64][65]), whereas others focus on a specific type of farm within a region (e.g., [60,61,[66][67][68][69][70][71][72][73][74][75][76][77]). Such studies have identified various 'rules of thumb' or principles that farmers use to guide their choices, such as autonomy, cooperation, or being flexible by adapting production practices, which can be linked to principles of resilience derived from theoretical frameworks (see [40,78]).…”
Section: Conventional Approaches To Farm Resilience: Substantialism Amentioning
confidence: 99%
“…Such studies often use in-depth interviews to ask farmers what disturbances they have perceived in the past, and how they have coped with and adapted to changes. Some studies have compared case studies from several countries (e.g., [63][64][65]), whereas others focus on a specific type of farm within a region (e.g., [60,61,[66][67][68][69][70][71][72][73][74][75][76][77]). Such studies have identified various 'rules of thumb' or principles that farmers use to guide their choices, such as autonomy, cooperation, or being flexible by adapting production practices, which can be linked to principles of resilience derived from theoretical frameworks (see [40,78]).…”
Section: Conventional Approaches To Farm Resilience: Substantialism Amentioning
confidence: 99%
“…Other strategies reported in the literature are: engaging in on-farm processing and off-farm employment, renting out or selling part of the land and rescheduling on-farm tasks, cautious and conservative investment decisions, introduction of niche crops, and diversification of market opportunities. All the strategies we identified fall under the reprofiling strategies [37][38][39][40]. Depending on the progress of the COVID-19 pandemic, the observed coping strategies might have to evolve into adaptation strategies if the crisis were to last much longer.…”
mentioning
confidence: 98%
“…Inherent in this work is the need to better understand how researchers and practitioners can utilize paired objective and subjective measures to understand current and emerging issues, and the broader types of investments and interventions that contribute to farm resilience at different scales. Since farm resilience studies incorporating subjective measures have largely been qualitative (Daugstad 2019;Perrin et al 2020), our study provides an example of how objective and subjective measures can be combined in the same quantitative study.…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is connected to the contradiction and mismatch in the scale at which challenges and resilience indicators are measured. While much of the farm resilience research focuses on macro-level challenges, studies tend to emphasize the micro-level variables associated with vulnerability and resilience, such as farmers socio-demographic characteristics, farm operation characteristics, farmers' actions and pre-disposition, and their adaptation strategies (Darnhofer et al 2016;Daugstad 2019;Diserens et al 2018;Greenhill et al 2009;Kangogo et al 2020). As scholars critiquing the resilience lens have argued (speaking about the application to agriculture and other topics), the de facto interpretation of this micro-level focus is to interpret resilience through an individual's deficits (Calo 2020;Cote and Nightingale 2012;Hall and Lamont 2013;Joseph 2013).…”
Section: Introductionmentioning
confidence: 99%